The AR storybook as multimodal teaching resource - Peña Acuña, Beatriz (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Recently, this teaching tool with augmented reality technology has appeared as a new resource in recent years. In this qualitative investigation, we intend to know what perceptions are obtained by 72 future teachers of Early Childhood Education once they experience these multimodal digital formats for themselves. Among the conclusions, they consider that the AR story is a multimodal tool with many qualities, suitable to be introduced to infants, playing a motivating role for the development of reading. In addition, these 3D stories make children learn while having fun.